2007
DOI: 10.1111/j.1471-4159.2007.04772.x
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline and riluzole brain disposition: interactions with p‐glycoprotein at the blood–brain barrier

Abstract: Amyotrophic lateral sclerosis is a neurodegenerative fatal disease. The only drug recognized to increase the survival time is riluzole(RLZ). In animal models, minocycline (MNC) delayed the onset of the disease and increased the survival time (in combination with RLZ). The objective of our work was to study the interactions between RLZ, MNC and the efflux pump p-glycoprotein (p-gp) at the blood-brain barrier. We investigated these two drugs as: (i) p-gp substrates by comparing their brain uptake in CF1 mdr1a ()… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…We showed mainly that P-glycoprotein (P-gp), the most influent efflux transporter at the BBB level, effluxes minocycline and riluzole out of the brain back to blood. We also showed that minocycline could inhibit P-gp functionality (15). Our results combined with Gordon's study aroused the question of a potential pharmacokinetic drug-drug interaction between riluzole and minocycline that could prevent the beneficial effect of this drug combination.…”
Section: Introductionsupporting
confidence: 56%
“…We showed mainly that P-glycoprotein (P-gp), the most influent efflux transporter at the BBB level, effluxes minocycline and riluzole out of the brain back to blood. We also showed that minocycline could inhibit P-gp functionality (15). Our results combined with Gordon's study aroused the question of a potential pharmacokinetic drug-drug interaction between riluzole and minocycline that could prevent the beneficial effect of this drug combination.…”
Section: Introductionsupporting
confidence: 56%
“…Therefore, riluzole induces a self-barrier to its own brain activity (Milane et al 2009). Minocycline, a tetracycline antibiotic, on the other hand, inhibits P-glycoprotein, another efflux pump, so that when administered with riluzole it results in higher riluzole brain levels in an animal model (Milane et al 2007). …”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In addition, levels of riluzole are four-to sixfold higher than plasma/serum levels after oral dosing in mice, rats, and monkeys, and high CNS levels persist for many hours after a single dose of riluzole (Colovic et al 2004;Maltese et al 2005;Martinet et al 1997;Milane et al 2009;Wu et al 2013). This high brain-to-blood concentration ratio is presumably due to the high lipid solubility of riluzole, although there is also evidence that riluzole is a substrate for blood-brain barrier transporters (Milane et al 2007(Milane et al , 2009. Riluzole concentration in the human brain after oral administration is not known; however, cortical excitability is altered for up to 24 h after a single dose of riluzole, even though plasma levels have dropped to ϳ5% of peak levels at that time (Schwenkreis et al 2000).…”
mentioning
confidence: 97%
“…Excretion of xenobiotics from brain tissue is at least partially regulated by the P-glycoprotein, found in high concentration in the luminal membrane of brain capillaries (Miller et al 2008). Inhibition of this transporter protein by minocycline or by gene knockout increases the brain concentration of riluzole severalfold (Milane et al 2007(Milane et al , 2009). This excretion mechanism probably accounts for the relatively long persistence of high concentrations of riluzole in brain tissue (Chow et al 2012;Milane et al 2009).…”
mentioning
confidence: 99%